Capabilities and the “Value” Flows of International Graduate Returnees and Their Networks - Pham, Lien (Journal of International Students, 2020)
There is no shortage of assumptions about the economic benefits of international education for international students, graduates, and their home countries. At the individual level, the success stories are about improved employability in the local labor market. These stories, though, are often filled with accounts of personal struggles and systemic barriers relating to cultural adjustment, institutional structures and political contexts of the workplace, lack of research environment, technological and industrial infrastructures, and stigmatization of international students in the home countries. At the national level, returning graduates’ acquired knowledge and skills are assumed to translate to quality human resources and national productivity that meet their country’s economic development needs. Yet, there are limited studies with conclusive evidence of improved human capital or increased productivity as a result of studying abroad. Although there is some attention to how sending countries can attract students back such as repatriation schemes, which stipulate conditions of study abroad scholarships, there remains little attention to evaluating the effectiveness of these initiatives. The context and contradictions of various institutional and national policies and different countries’ development needs, as well as graduates’ circumstances that impact their choices and experiences, point to multifaceted outcomes and impacts of international education. Important as they are, contributions of returning international graduates to their society remain curiously underresearched and undertheorized.This lack of attention to returnees is, in part, due to the focus of internationalization of higher education on revenue and the global reputation of universities rather than its impacts on the lives of international students, graduates, or their communities. But as de Wit (2020) pointed out, there has been an emerging shift in the last few years toward the role of international education in making contributions to society. There are various dimensions and explications of this shift. One way is for research and policies to articulate, implement, and evaluate international graduates’ knowledge transfers and skills application when they return home. Given that the majority of international students come from developing countries and return home after completing their overseas studies, it is important to understand the impacts of international education for these returnees in terms of trajectories, economic and community integration experiences, and contribution to their countries’ development needs. In this regard, student mobility should be studied as a holistic process of moving, studying, working, and engaging in local communities across national borders before, during, and after their international studies. These studies should be conducted in ways that can shed light on students and graduates’ opportunities and practices, and capture overlapping effects of institutional and national policies and structures on students’ choices and experiences.Amartya Sen’s (1999) capability approach can be a starting point for these types of tracer studies or policies because it places the graduate returnees at the center of the research or policy framework (Pham, 2015). In my research about Vietnamese international graduates’ experiences when they returned home, I asked returnees to reflect and articulate different ideas from abroad and locally in relation to their choice of employers and community activities. Their accounts revealed different values about overseas-acquired knowledge and skills that were contingent on their social and professional networks, standards and practices in different sectors, and cultural environment of their organizations. These values, when shared, form the capabilities set that allow them to mobilize their knowledge and skills and enable improved standards of their work practices or community development (Pham, 2019).For these graduates, understanding their capabilities is more than recognizing the types of knowledge and skills that they can apply or that are relevant to the organizational needs, although this recognition is important for gaining access to employment or community volunteer work. Capabilities are about their agency—how they shape their own lives and bring about change—rather than being shaped or instructed on how to think (Pham, 2019). Their contributions to society are not a universal set of checkpoints. They reflect the social, cultural, political, and economic specificities that condition their ability to create value in work, education, or civic activities. This process of creating and mobilizing value is pluralistic as they encounter traditional values that are different from those acquired during their sojourns. It also involves creating new networks in their home countries, or leveraging those acquired abroad to share and exchange information, reflecting on the new and old values and how these values mediate and enhance their social positions. These networks of co-workers and managers, volunteers and community leaders, friends in professional associations, and alumni groups also invite contestation and conflict because values are not always shared or appreciated in reciprocal ways. The returnees’ capabilities stem from the linkage effects of their overseas-acquired skills and knowledge and the cultural values and social norms of these networks—the “value flows”—in knowledge transfers in specific situations. Value flows are potentialities of international graduates, which may be created and mobilized through linkages of graduates with their networks. The effects of these linkages are co-creation and mobilization of knowledge.The practical implications of a capability-based policy framework are about creating mechanisms for international graduates to build actual collaborative relations so that they can create and mobilize values with their networks inside and outside their organizations, with government bodies, and broader society. A values-based analysis of returning international graduates has many potential benefits in a network-based society like Vietnam or countries with similar cultures, in terms of identifying the flows of skills and knowledge between returnees and their networks, and the extent to which these value flows enhance or hinder returnees’ capabilities to contribute to their society. A capability-based policy can also be applied to design and evaluate the potential contribution of returnees in other aspects of development such as capacity development of educators, civic workers, or public administrators.According to Sen (1999), a role of education is to expand human agency and freedom, both as an end in itself and as a means of further expansion of freedom. Freedom here refers to capabilities or opportunities to apply and develop students and graduates’ knowledge and skills in ways that are valuable for themselves and for their societies. Thus, learning to expand freedom and agency should encourage people to examine themselves and their place in the world, their subjective conditions, and the forms that they can use to imagine and develop their own futures. This is a powerful contribution that the capabilities approach can bring to argue for the vision and processes of international education itself, but also for nuanced understandings of the myriad ways in which international graduates can harness their learning to contribute to the world that they live in. This link between international education and expansion of capabilities requires policy and research design beyond economic measures or quantitative indicators to understand both intrinsic and instrumental purposes of education for human flourishing. It is also a tool for reflection and tolerance of differences across cultures and traditions in their pathways to ethical development.